Multilocus environmental adaptation and population structure in the Cerrado gecko Gymnodactylus amarali (Sauria, Phyllodactylidae) from Serra da Mesa Hydroelectric Plant, Central Brazil - Miranda, Rogério Benevides; Brandão, Reuber Albuquerque; O’Connell, Kyle; Colli, Guarino Rinaldi; Tonini, João F. R.; Pyron, R. Alexander (Frontiers in Ecology and Evolution, 2023)
Contrasting environmental conditions across geographic space might promote divergent selection, making adaptation to local biotic and abiotic conditions necessary for populations to survive. In order to understand how populations adapt to different environmental conditions, studies of local adaptation have been largely used as an interface to address ecological and evolutionary questions. Here, we studied populations of Gymnodactylus amarali (Phyllodactylidae) isolated in rapidly created artificial islands. We combined a genotyping-bysequence (GBS) survey and redundancy analyses (RDA) to investigate genotype-environment associations (GEA), while DAPC, Fst, and Admixture analyses were used to determine genetic structure. Our hypothesis is that G. amarali populations on the islands are going through a local adaptation process and consequently becoming genetically different from the populations on the mainland. Our results indicate that geographic and environmental differences are related to genetic variation, as we detected the presence of two or three distinct genetic lineages in Serra da Mesa, Minaçu, and Colinas do Sul. Fst analysis shows moderate isolation between Serra da Mesa and Minaçu (0.082). The RDA pointed out potential local genetic signal correlated with temperature and precipitation. We identified 230 candidate loci associated with the environment and at least two locally structured subpopulations (Serra da Mesa and Minaçu) show significant association with environmental variation.